O desvelar da verdade: o acontecimento originário da arte, verdade e linguagem na filosofia de Martin Heidegger - Oliveira, Bruno José do Nascimento (2023)
This thesis has as its centrality to approach the theme of art and truth in Martin Heidegger, with the aim of supporting the construction of an ontology of the work of art linked to the search for the meaning of being. The philosopher starts with a retake of the Greek expression aletheia when discussing the theme. Therefore, intending to demonstrate the construction process of this Ontology that relates two terms until then thought of independently, our research goes through the developments of the fundamental ontology of Being and Time (1927) and the context of the turning point (Kehre) of his thought (1930), in which the question of being could no longer be thought through concepts, which only encompassed logical statements, so, Heidegger decides to go beyond this way of thinking, where he is faced with poetry, to transit through the extraordinary regions of being. To reach the proposition of this thesis, we initially sought to map how the question of truth emerges in order to characterize it as a fundamental intuition initiated in Being and Time and which will guide all of Heidegger's subsequent production. Thus, § 44 is configured as crucial in this thesis. Because, in it, we find the initial treatment given to the question of truth as disclosure, distinguishing it from the truth as adequacy, supported by the philosophical tradition. Based on this connection, we explain the turning point in the author's thought. Instead of proceeding to his fundamental Ontology in the perspective of the meaning of being, the ontological horizon of his thoughts diverted to the truth of being. Secondly, it is evident how the work of art, thought through the truth, is a free expression of the being, providing the understanding of the truth under the ontological prism of the conflict between world and earth. In this, the fundamental meaning of art reveals itself as an origin, an original scope that makes possible the installation of a world, since art removes man from his everyday world and enables him to enter into the truth of the work. Art presents itself as a possible way of broaching the event of truth as a disclosure. Heidegger develops his reflections on this topic in his text The Origin of the Work of Art (1935/36), in which the philosopher presents us, together with the question of the essence of language and poetry, the guiding notions of his ontological conception of the work of art, which in turn, diverges from the traditional theories of Philosophical Aesthetics. We use this work to structure the central locus that guides this thesis without disregarding other writings and works of relevant importance for this research. In this way, the investigation intends to point out that the work of art emerges as the privileged access to truth, being the correlation between art and truth, which implies the disclosure of being, which makes possible through the Ontology of works of art, new horizons of sense.